Intra-Couple Wealth Inequality: What's Socio-Demographics Got to Do with it? - Miriam Rehm; Alyssa Schneebaum; Barbara Schuster (European Journal of Population, 2022)
Existing literature shows that on average and across countries, men have higher levels of wealth than women. However, very little is known about the gender-specific wealth gap within couples . This paper studies this phenomenon for the first time in Austria. The particular focus of the paper is on the relationship between the socio-demographic characteristics of the couple and the couple's gender wealth gap. We focus on how age, education, marital status, fertility, migratory background, and the gender of the respondent are related to the wealth gap within a couple. In both bivariate and multivariate analyses, we find evidence in support of the hypothesis that bargaining power plays an important role in the intra-couple gender wealth gap in Austria. Immigrant women living in a couple with native men, and, among natives, couples in which the man is much older on average, have larger gender wealth gaps. Furthermore, couples in which the woman is the "financially most knowledgeable person" in the household have consistently lower gender wealth gaps.
Keywords: 300; Wealth; Gender wealth gap; Demographics; Bargaining power